Pengaruh Soft Skill Terhadap Kinerja Pegawai Aviation Security Di Bandar Udara Internasional Mopah Merauke Papua - Christine Vira Kirwelakubun; Suprapti (Lembaga Pengembangan Kinerja Dosen, 2023)
With the increasing demand for air transportation services, it must be accompanied by an increase in aviation safety and security, both safety and security in airspace, aircraft and airports. Airport security is determined by the active role of Aviation Security to implement security programs set by the government. Increasing the quality of AVSEC is very urgent and needs to be carried out in a planned, directed and sustainable manner in order to increase capability and professionalism. To support this, it is necessary to have soft skill behavior to guide performers to improve and form quality attitudes and behaviors that can produce maximum performance in order to realize goals and benefits properly. The purpose of this study was to determine the influence of soft skills on the performance of aviation security and to find out how much influence soft skills have on the performance of aviation security at Mopah Merauke International Airport, Papua. This research used a quantitative method using the Non Probability Sampling technique using a saturated sample. The sample used was 30 respondents, the results of distributing questionnaires to all Avsec employee respondents at Mopah Merauke International Airport, Papua. Retrieval of data on the number of samples using a survey with an instrument in the form of a questionnaire. Data were analyzed using simple linear regression, T test and coefficient of determination with soft skills as the independent variable and Avsec employee performance as the dependent variable which were processed using the SPSS Version 26.0 application. The results showed that the t count > t table with a value of 7.987 > 0.374 with a significant level of 0.05, so it can be concluded that Ho is rejected and Ha is accepted which means that there is an influence of soft skills on the performance of Avsec employees at Mopah Merauke International Airport, Papua partially accepted . The percentage based on the coefficient of determination test shows that the R square is 0.695. This means that the influence of soft skills on the performance of Avsec employees at Mopah Merauke International Airport, Papua is 69.5%.